A study on Soft Pre-Open Sets using γ Operation - Jamil, Jamil Mahmoud (Iraqi Journal of Science, 2021)
The concept of strong soft pre-open set was initiated by Biswas and Parsanann.We utilize this notion to study several characterizations and properties of this set. We investigate the relationships between this set and other types of soft open sets. Moreover, the properties of the strong soft pre-interior and closure are discussed. Furthermore, we define a new concept by using strong soft pre-closed that we denote as locally strong soft pre-closed, in which several results are obtained. We establish a new type of soft pre-open set, namely soft pre-open. Also, we continue to study pre- soft open set and discuss the relationships among all these sets. Some counter examples are given to show some relationships obtained in this work.